A schistosomiasis research agenda. - Daniel G Colley; W Evan Secor (Public Library of Science (PLoS), 2007)
There is a long and rich history of research and control in the field of schistosomiasis that has resulted in major scientific and public health accomplishments. Examples of such findings and accomplishments include immunologic regulation in chronic infections, the association of helminth infections with Th1-regulating Th2-type immune responses, the critical role of interleukin-13 in fibrogenesis, and the development and validation of the "dose pole" for determining praziquantel dosages in the field. Perhaps in part because of this broad and successful history, those who work on schistosomiasis come from a wide variety of backgrounds and interests. While such variety is enriching to the field, it sometimes results in diverse opinions about which of the many research opportunities should be pursued. Such diversity, we believe, has at times led to a divisiveness that has harmed overall progress in the field. Partly in response to such events, we have worked with as many of those interested in schistosomiasis as we could identify to develop what we feel is a comprehensive and cohesive agenda for schistosomiasis research.